Crystalline phases in nylon-11: studies using HTWAXS and HTFTIR - Nair, S. S.; Ramesh, C.; Tashiro, K. (Macromolecules, 2006)
Nylon-11 was crystallized into different crystalline phases by appropriate methods. The chance in the structure during heating was monitored in situ by wide-angle X-ray scattering (WAXS). The alpha phase obtained by precipitating nylon-11 in 1,4-butanediol started transforming into the pseudohexagonal phase on heating, but the transformation was not fully completed before melting. The melt crystallized sample at 175 degrees C gave the pseudohexagonal phase, which transformed into the alpha' phase on cooling to room temperature at about 100 degrees C. The d spacing of the 00 1 reflection also showed a change at the transition temperature. The melt-quenched sample showed the pseudohexagonal phase, which did not change during heating, but on cooling transformed into alpha' phase. The gamma phase was obtained by casting nylon-11 in trifluoroacetic acid (TFA), and it changed into the pscudohexagonal phase at about 110 degrees C on heating. The d spacing of the 001 reflection depended on the way in which it was obtained. The studies have shown that nylon-11 is one of the few nylons that exhibit an extensive degree of polymorphism. High-temperature Fourier transform infrared spectroscopy (HTFTIR) studies revealed, apart from the conformational differences between various phases of nylon-11, some information on the formation of the gamma phase.